Nicotine dependency of adult male smokers and it’s socio-economic determinants - Swe, Swe Latt; Mohd Rus, Razman; Ab Rahman, Jamalludin; Nasreen, Hashima E; Phyu, Htike Myat; Abd. Aziz, Karimah Hanim (2015)
INTRODUCTION: Most smokers become dependent both physically and psychologically within a few years of daily smoking because of its major chemical component of nicotine in tobacco. Nicotine dependence is occurred at any time which affects on successful smoking cessation. The aim of the study was to measure the prevalence of nicotine dependence (ND) among adult male smokers and influences of socio-economic characteristics on it. METHODS: A cross-sectional study was conducted among 297 adult males participants with aged ≥18 years and who were recruited purposively from the house-holds which were selected using simple random sampling at FELDA Bukit Goh, Kuantan, Pahang in February 2015. Smoking and nicotine dependence status of the participants were assessed using a self-administered questionnaire in which consisted of modified smoking and tobacco use questions used in National Health Interview Survey and validated Malay version of Fagerstrom Test for Nicotine Dependence (FTND-M) assessment questionnaires. Fishers’ exact test, ANOVA and median test were applied to infer association between nicotine dependency and socio-economic (SE) variables (age, education, occupation, income and marital status).